Comparison of ‘Mental training’ and physical practice in the mediation of a structured facial examination: a quasi randomized, blinded and controlled study - Nelskamp, Arne (BMC Med Educ, 2021)
BACKGROUND: The correct performance of a structured facial examination presents a fundamental clinical skill to detect facial pathologies. However, many students are not adequately prepared in this basic clinical skill. Many argue that the traditional ‘See One, Do One’ approach is not sufficient to fully master a clinical skill. ‘Mental Training’ has successfully been used to train psychomotor and technical skills in sports and other surgical fields, but its use in Oral and Maxillofacial Surgery is not described. We conducted a quasi-experimental to determine if ‘Mental Training’ was effective in teaching a structured facial examination. METHODS: Sixty-seven students were randomly assigned to a ‘Mental Training’ and ‘See One, Do One’ group. Both groups received standardized video instruction on how to perform a structured facial examination. The ‘See One, Do One’ group then received 60 min of guided physical practice while the ‘Mental Training’ group actively developed a detailed, stepwise sequence of the performance of a structured facial examination and visualized this sequence subvocally before practicing the skill. Student performance was measured shortly after (T1) and five to 10 weeks (T2) after the training by two blinded examiners (E1 and E2) using a validated checklist. RESULTS: Groups did not differ in gender, age or in experience. The ‘Mental Training’ group averaged significantly more points in T1 (pE1 = 0.00012; pE2 = 0.004; dE1 = 0.86; dE2 = 0.66) and T2 (pE1 = 0.04; pE2 = 0.008, dE1 = 0.37; dE2 = 0.64) than the ‘See One, Do One’ group. The intragroup comparison showed a significant (pE1 = 0.0002; pE2 = 0.06, dE1 = 1.07; dE2 = 0.50) increase in clinical examination skills in the ‘See One, Do One’ group, while the ‘Mental Training’ group maintained an already high level of clinical examination skills between T1 and T2. DISCUSSION: ‘Mental Training’ is an efficient tool to teach and maintain basic clinical skills. In this study ‘Mental Training’ was shown to be superior to the commonly used ‘See One, Do One’ approach in learning how to perform a structured facial examination and should therefore be considered more often to teach physical examination skills. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12909-021-02603-0.